Automated Data Labeling and Anomaly Detection Using Airborne Sound Analysis - Mühlbauer, Matthias; Würschinger, Hubert; Polzer, Dominik; Ju, Shu; Hanenkamp, Nico (Procedia CIRP, 2020)
Anomaly detection is facing the challenge of generating a maximum of information with a limited number of sensors in production machines and minimal effort of data analysis. Machine operators are often able to perceive changes acoustically and based on experience. In order to imitate this intelligent human capability, a systematic methodology has been developed in this work. Firstly, an introduction to this topic will be given and the acoustic sensor set up as well as the data preprocessing will be described. Secondly, an approach for automatic data labeling as an input for the intelligent anomaly detection will be presented. Using a model-based approach, anomaly detection is performed in the next step. This allows not only the detection of gradual and sudden process changes but also systematic problem solving. Finally, the anomaly detection will be validated for cutting processes.<br
Keywords: Anomaly Detection; Automated Data Labeling; Process Monitoring; Airborne Sound; Cyclic Production Processes; Cutting Processes

Cutting force and vibration prediction of milling processes regarding the nonlinear behavior of cascade controlled feed drives - Ju, Shu; Gross, Daniel; Hanenkamp, Nico (Production Engineering, 2022)
Milling processes are characterized by their high degree of flexibility regarding shape creation and thus occur in many value adding processes in the electrical and mechanical engineering industry. To facilitate the systematic prediction and the efficient optimization of the process performance, a holistic simulation model of the milling process with cascade controlled feed drives is developed. The integrated model consists of two subsystems, namely the feed drive model and the process model. In the feed drive model, the dynamic models of the electric motors, the serially connected torsional oscillators of the mechanical elements and the cascade control system are established. In this model, the coordinate point of the milling tool is computed at each discrete time step and assigned to the process model. The cutting forces and the corresponding load torques are calculated in the process model and sent back to the feed drive model. In addition, practical validation of the complete system has been conducted both in the time and the frequency domain. The simulation results yield an accurate prediction of the tooth passing frequency with a variance of less than 1%. Moreover, the influence of the cascade control parameters and the nonlinear behavior of the electric motor on the process vibrations have been experimentally verified.<br
Keywords: Milling process simulation; Cascade control model; Cutting force prediction; Vibration prediction

Energieeffizienz durch Oberschwingungsreduzierung*/Energy efficiency through harmonic distortion reduction – Harmonics-minimized control strategy in production machines - Ju, Shu; Hanenkamp, Nico (wt Werkstattstechnik - Online, 2019)
Oberschwingungen ausgelöst durch frequenzgeregelte Antriebe wirken sich stark negativ auf den Energieverbrauch aus. Diese Oberschwingungen verstärken sich immer dann, wenn schnelle Drehzahländerung aus Produktivitätsgründen notwendig wird. Eine neue Steuerungsstrategie wird entwickelt. Durch Erhöhung des Grundschwingungsanteils im Motorsteuersignal lässt sich eine bis zu 20 % höhere Energieeffizienz erreichen. Ein Modell einer Bibliothek wird entwickelt. </
Keywords: Energieeffizienz; Steuerungstechnik

Energy Efficiency in Production Machines Through Harmonic Distortion Reduction - Ju, Shu; Hanenkamp, Nico (IEEE PES Asia-Pacific Power and Energy Engineering Conference, 2019)
With the growing trend towards massive utilization of power electronics, the effect of harmonic distortions on not only power grids but only other system components is non-negligible. In this document, the source and effect of harmonic distortions are described. Latest state of harmonic distortion reduction technologies was researched and briefly depicted. Because of the technological limitations of the current methods, a control strategy by adjusting motor speed change trajectories in order to generate less harmonic distortions in motor acceleration and deceleration processes has been developed. The implementation needs only control software changes and no hardware installation. Based on sufficient simulation results, experiments have been carried out on a lab-constructed motor test bench. Optimized motor speed change trajectories with time-delayed transfer elements have been adjusted and put into operation, ensuring up to 20% energy saving potential during the motor speed changing phases. Energy efficiency can be achieved by applying the optimization method to any use case of power electronic actuators characterized by a highly dynamic machining proces
Keywords: Energy efficiency; harmonic distortion; machining; optimization methods; variable frequency drives

Milling Strategy Design to Improve Vibration Behavior, Tool Wear and Surface Roughness in Machining - Ju, Shu; Hanenkamp, Nico (Proceedings of WCSE 2022 Spring, 2022)
Uncontrollable vibration behavior during the milling process impairs the surface quality of the workpiece and escalate the machine damage as well as machine and tool wear. In this work, the impact of various milling strategies with control optimization for three different types of milling operations are studied. To objectively quantify the process quality, the machining time, the width of tool wear marks and the surface quality after each experiment as well as the vibration amplitude and the bending moment of the tool holder during the process have been measured and evaluated. For every milling type, three milling strategies with three iterative experiments each have been carried out. As a result, a database with vibration-related data and information for different milling strategies has been established. Thus, the machining process of workpieces with diverse geometric elements and the corresponding manipulated variables can be assessed regarding the vibration and tool wear behavior. Based on the experimental results, the potentials of the vibration-minimized milling strategies and tool path design in enhancing the process stability, the productivity and the tool life can be verified.<br
Keywords: Milling operations; chatter suppression; process optimization

Model-Based Correlation Analysis of Machine Control Parameters and Process Vibration Amplitudes by the Example of Milling - Ju, Shu; Reitenspieß, Max; Zhang, Kai; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCMS 2022, 2023)
In machining processes, system-immanent process vibrations lead not only to lower surface quality of workpieces but also to the degradation of the machine and tool wear. Effectively minimizing process vibration amplitudes without costly software or hardware add-ons is a research topic that demands further investigation. In this regard, this article focuses on the further development of a holistic milling process model as well as the experimental and simulation-based vibration analysis. The interaction between the nonlinear behaviors of the cascade controlled electric motors and the process parameters are practically evaluated. Moreover, based on the experimental and simulation results, a correlation analysis of the machine control parameters and the process vibration amplitude has been implemente
Keywords: integrated simulation system machining process vibration cascade control

Ressourceneffizienz durch Schnittstellenoptimierung - Hanenkamp, Nico; Ju, Shu (Technik in Bayern, 2019)